2016
DOI: 10.1007/s00404-016-4046-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of primary caesarean delivery: comprehensive management of dystocia in nulliparous patients at term

Abstract: Comprehensive management of dystocia enabled us to achieve a reduction in iatrogenic interventions in labor while maintaining good neonatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
0
19
0
1
Order By: Relevance
“…In this perspective, the hyperbolic curve deriving from cervical dilation /time ratio becomes a screening tool and no longer a diagnostic tool to decide when to intervene with medical procedures (6,19). 11.1% of midwives who would intervene with artificial rupture of membranes at the diagnosis of dystocia, probably, as indicated by a comment on the questionnaire, would do it in accordance with NICE indications, that support rupturing the membranes at the time of delay in cervical dilation after 4 hours of unchanged finding ( figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…In this perspective, the hyperbolic curve deriving from cervical dilation /time ratio becomes a screening tool and no longer a diagnostic tool to decide when to intervene with medical procedures (6,19). 11.1% of midwives who would intervene with artificial rupture of membranes at the diagnosis of dystocia, probably, as indicated by a comment on the questionnaire, would do it in accordance with NICE indications, that support rupturing the membranes at the time of delay in cervical dilation after 4 hours of unchanged finding ( figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Neuraxial techniques are used to provide analgesia for labour [8, 9] and anaesthesia for surgical delivery. Therefore, complications associated with neuraxial techniques are sometimes seen even in pregnant patients.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to progress in labour is often associated with dysfunctional uterine contraction, and is the most common indication for primary CS, accounting for 50% of CSs in nulliparous women and for the majority of repeat CSs in labour (Ragusa et al . ). It has been suggested that poor uterine contractile function may be responsible for the slow labour, increased need for CS, and increased post‐partum haemorrhage reported in the labour of first‐pregnancy women over 40 years of age (Bianco et al .…”
Section: The Need To Augment Contractions and For Caesarean Delivery mentioning
confidence: 97%